2017
DOI: 10.3126/ijasbt.v5i1.16982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Replacement of Fish Meal by Soybean Meal on Growth of Oreochromis niloticus (Linné, 1758) Juvenile under High Temperature Treatment for Masculinization

Abstract: Two experiments were conducted consecutively in triplicates to evaluate and compare the impact of different feeds on survival rate and growth performances of Oreochromis niloticus larvae during both the heat treatment for thermal masculinization and the subsequent juvenile stage. A commercial feed containing fishmeal with 32.38% crude protein (CFA) and an experimental feed with 25.48% crude protein (EFB) where fishmeal was entirely replaced by soybean meal were tested. In the first experiment, larvae of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These results are consistent with the results of Furuya et al (2004); Zhou and Yue (2010); Mahboob (2014) and Al-Thobaiti et al (2018) which revealed that the replacement of fishmeal by plant protein sources improved fish performance to achieve better growth without any negative impact on fish, not only that but also reduced production costs, thereby increasing the net profit. In contrast, Yatawara and Hettiarachchi (2006) and Boussou et al (2017) mentioned that there were no significant differences (P> 0.05) in growth performance and feed utilization parameters of fish feed containing fishmeal or feed containing different replacing percentage by soybean meal (10-50%) for GIFT tilapia, or diets containing 0%, 16.54%, 33.18% and 66.77% as the protein source for the African catfish, Clarias gariapinus (Ugwoke, 2013) and up to 30% without any reduction in growth rate of Egyptian sole (Bonaldo et al, 2006). Soltan et al (2001) reported that after 16 weeks' experimental period, average body weights of Nile tilapia fish fed diets containing different percentages of soybean meal (0%, 25%, 50%, 75% and 100%) were 58.…”
Section: Body Weightmentioning
confidence: 90%
“…These results are consistent with the results of Furuya et al (2004); Zhou and Yue (2010); Mahboob (2014) and Al-Thobaiti et al (2018) which revealed that the replacement of fishmeal by plant protein sources improved fish performance to achieve better growth without any negative impact on fish, not only that but also reduced production costs, thereby increasing the net profit. In contrast, Yatawara and Hettiarachchi (2006) and Boussou et al (2017) mentioned that there were no significant differences (P> 0.05) in growth performance and feed utilization parameters of fish feed containing fishmeal or feed containing different replacing percentage by soybean meal (10-50%) for GIFT tilapia, or diets containing 0%, 16.54%, 33.18% and 66.77% as the protein source for the African catfish, Clarias gariapinus (Ugwoke, 2013) and up to 30% without any reduction in growth rate of Egyptian sole (Bonaldo et al, 2006). Soltan et al (2001) reported that after 16 weeks' experimental period, average body weights of Nile tilapia fish fed diets containing different percentages of soybean meal (0%, 25%, 50%, 75% and 100%) were 58.…”
Section: Body Weightmentioning
confidence: 90%